SOCIAL AND EMOTIONAL IMPACT OF ONLINE EDUCATION: A LITERATURE ANALYSIS - Dedi Zulkarnain Pulungan; Cipto Duwi Priyono; Mohammad Ahmad Bani Amer (CV. Adiba Aisha Amira, 2025)
Online education has become an increasingly popular learning method, especially in the digital and post-pandemic era. However, its impact on learners' social and emotional aspects is still a topic that needs further research. This literature analysis aims to understand the effect of online education on students' social interaction and emotional well-being. The results show that online education can lead to social isolation due to limited face-to-face interaction and affect students' interpersonal skills. In addition, emotional aspects such as stress, anxiety and technology adaptation challenges are significant impacts, although some students are able to experience benefits such as increased self-confidence. The conclusion of this analysis emphasises the need for a holistic approach that includes social support, interactive programmes and teaching strategies that focus on emotional wellbeing to maximise the potential of online education.